The encyclopedia of addictions and addictive behaviors - Gwinnell, Esther; Adamec, Christine A. (Facts on file library of health and living, 2006)
Containing some 300 alphabetically arranged entries, this reference covers signs, symptoms, and causes of addictive behaviors and discusses treatments and therapies. It is written at a level accessible to general readers, and it may be useful for counselors and others who need basic information or a starting point for research on a broad range of topics. Entries range from a few paragraphs to several pages and include references and cross-references. Tables containing statistical information on addictions among various populations are found in the appendices, as are lists of state substance abuse agencies and other relevant organizations. Gwinnell is a psychiatrist affiliated with Oregon Health Sciences U.; Adamec is a seasoned writer of medical self-help books